STRATEGI GURU DALAM MENGAJAR BAHASA ARAB DI MTS MIFTAHUDDIN RANTAU KUJANG JENAMAS (AL-I’ROBY: Jurnal Pendidikan Bahasa Arab Dan Kebahasaaraban, 2025)
To achieve quality education, it is essential to implement effective strategies in the teaching and learning process, particularly regarding teachers' language teaching strategies. This study aims to identify the learning strategies used by Arabic language teachers in teaching Arabic at MTs Miftahuddin Rantau Kujang Jenamas and to determine the supporting and inhibiting factors teachers face when teaching Arabic. The research approach used is qualitative with a descriptive research type. The research subjects are Arabic language teachers at MTs Miftahuddin Rantau Kujang Jenamas, while the research object is the strategies applied by the teachers in teaching Arabic. The results show that the strategies used by the teachers include: a) Simulation Strategy; b) Question and Answer Strategy; c) Repetition Strategy; d) Memorization Strategy; and e) Small Group Strategy. The supporting factors in the Arabic teaching strategies are the presence of competent teachers and high motivation. Meanwhile, the main inhibiting factor is the less conducive learning environment.